Strategi Penurunan Kehilangan Air Melalui Analisis Neraca Air dan Indikator Kinerja Air Tak Berekening (ATR) Pada Perumda Air Minum Kota Padang - Romzuddin, Muhammad; Yuniarto, Adhy (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Improving water access in Indonesia requires reducing the Non-Revenue Water (NRW) level. One of Sumatra's largest water enterprises, Perumda Air Minum Kota Padang, has an NRW of 27.98% in 2024, compared to the national target of 25%. This research aimed to use the analysis of NRW performance indicators and water balance to develop a plan for minimizing water loss. The descriptive exploratory method is employed. According to the water balance analysis, Perumda Air Minum Kota Padang's NRW level in 2024 was 27.98%, or roughly 14,113,007 m ³. This consists of physical losses 8,229,365 m ³ (16.45%) and non-physical losses of 5,694,546 m ³ (11.29%). The NRW performance indicator was categorized in performance category C (poor NRW condition), but the physical water loss was categorized in performance category D (extraordinary resource wastage). To minimize water loss, it is advised to check for unauthorized connections, test and replace meters that are more than five years old, and replace the pipe network that has exceeded its technical life.